2016
DOI: 10.1002/2016ja022962
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic ray variations in the inner heliosphere from solar distances less than 0.5 AU: Measurements from the MESSENGER Neutron Spectrometer

Abstract: The Neutron Spectrometer (NS) on board NASA's MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft is sensitive to galactic cosmic ray (GCR) protons greater than 125 MeV. During the MESSENGER orbital mission of Mercury, which lasted from March 2011 to April 2015, the NS made continual measurements of GCR variations, which represent the first long‐term GCR measurements for solar distances less than 0.5 AU. These relative GCR variations are compared to GCR variations measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…(3) As these data cover a wider range in time, the GCR flux varies considerably during the duration of the measurements, which leads to larger systematic variations in epithermal neutron production than those in Lawrence et al (). The measurement of GCR variability at Mercury used here is taken from Lawrence et al (), and the empirical correction for the changing GCR flux is described below. (4) Following Peplowski, Bazell, et al (), we implemented a two‐dimensional correction for angle‐ and altitude‐dependent NS‐viewing response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) As these data cover a wider range in time, the GCR flux varies considerably during the duration of the measurements, which leads to larger systematic variations in epithermal neutron production than those in Lawrence et al (). The measurement of GCR variability at Mercury used here is taken from Lawrence et al (), and the empirical correction for the changing GCR flux is described below. (4) Following Peplowski, Bazell, et al (), we implemented a two‐dimensional correction for angle‐ and altitude‐dependent NS‐viewing response.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid spurious results, data acquired during solar energetic particle (SEP) events were removed before the data were used. Following earlier studies (Lawrence et al, 2013(Lawrence et al, , 2017, the duration of these events was determined manually by looking through the spectra for increased background (see the list of SEP events given in Lawrence et al, 2016). Similarly, those data acquired during energetic electron events (EEEs; Lawrence, Anderson, et al, 2015;Nikoukar et al, 2018) were also removed as they complicate the derivation of neutron count rates.…”
Section: Messenger Epithermal Neutron Data Set Cutsmentioning
confidence: 99%
“…It has been shown that there is a radial gradient of GCRs of about ∼ 3%/AU (e.g. Webber and Lockwood 1999;Gieseler and Heber 2016;Lawrence et al 2016). Recently, Marquardt et al (2018) used Helios E6 data to show that the gradient of the anomalous cosmic ray oxygen is increasing with decreasing distance to Sun.…”
Section: The Basic Diffusion Modelmentioning
confidence: 99%
“…Heber et al (2013) included STA and STB proton time profiles for a single energy range in a figure, displaying the longitudinal extent of the event. The event was also observed by the MESSENGER spacecraft orbiting around Mercury, which, at the time of the event, was at a heliocentric distance of 0.34 au (Lawrence et al 2016). Battarbee et al (2018) investigated the time series of proton measurements from MESSENGER using its neutron spectrometry.…”
Section: Introductionmentioning
confidence: 99%